Inflammatory cardiovascular risk markers and silent myocardial ischemia in type 2 diabetic patients - Malešević, Gabrijela; Popović-Pejičić, Snježana; Marković, Aleksandra; Soldat-Stanković, Valentina (Vojnosanitetski pregled, 2022)
Background/Aim. A special feature of coronary heart disease (CHD) in patients with type 2 diabetes mellitus (T2DM) is that it is often asymptomatic and occurs as a consequence of cardiovascular autonomic neuropathy. Dysregulation of the autonomic nervous system is associated with elevated values of inflammatory markers such as high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6), which accelerate atherosclerosis and the occurrence of cardiovascular complications in patients with T2DM. The aim of the study was to evaluate the importance of determining inflammatory cardiovascular risk markers IL-6 and hs-CRP in screening for the presence of CHD in asymptomatic patients with T2DM. Methods. The study included 169 patients with T2DM without any symptoms and signs of CHD. Ergometric testing proved or ruled out the presence of silent CHD. The levels of hs-CRP and IL-6 were determined by ELISA. Results. IL-6 values were significantly higher in patients with a positive ergometric test (6.83 ± 1.99 pg/mL) compared to patients with a negative ergometric test (3.04 ± 1.39 pg/mL) (p < 0.001). We also found that hs-CRP values in patients with a positive ergometric test were significantly higher compared to patients with a negative ergometric test (6.37 ± 2.25 vs 1.67 ± 1.41 mg/L; p < 0.001). Combinations of IL-6 and hs-CRP with age, HbA1c values, and duration of diabetes, presented through three binary logistic regression models, are significant predictors of silent CHD proven by ergometric testing, ie, with their increase, the probability of a positive ergometric test also increases (p < 0.01). The sensitivity of the associated finding of elevated IL-6 and hs-CRP values in the detection of silent CHD by ergometric testing was 90%, and the specificity was 86%. Conclusion. Hs-CRP and IL-6 are significant predictors of silent CHD, and their determination could be recommended for improving cardiovascular risk stratification in asymptomatic patients with T2DM.